Investigating the Income Inequality in Indonesia: An Application of Autoregressive Distributed Lag Approach - Zulfa Nazli; Abd. Jamal; Muhammad Nasir (International Journal of Business, Economics, and Social Development, 2021)
This study investigates the effect of economic growth, urban population, unemployment, and human capital on income inequality in Indonesia. Annual data collected from World Development Indicator (WDI) is used from 1984 to 2019. The analytical method of this research is Autoregressive distributed lag (ARDL) to examine the short and long-term relationships. The results show that economic growth positively and significantly affects income inequality in the short and long term. The urban population variable has a significant negative effect in the short term but not in the long term. The unemployment variable has a significant positive effect in the long run. Finally, human capital negatively affects the short term while not in the long term. Based on these findings, it is recommended that the government stabilize inequality by increasing progressive taxes, creating jobs, providing soft skills training beyond formal education, and socializing the concept of commuter work.